High pressure cold spray (hpcs) process as coating treatment for magnesium chassis: an overview - Nooririnah, Omar; muhamad azwar, azhari; Umar , Al-amani; Yusliza, Yusuf (Trans Tech Publications, 2015)
Magnesium, Mg and its alloys have excellent physical and mechanical properties for a number of applications. Mg approximately 35% lighter than aluminum and has exceptional stiffness and damping capacity. Disadvantage of this metal and its alloys are highly susceptible to corrosion, particularly in salt-spray conditions and very susceptible to surface damage due to impact. This paper is an outcome of project to address corrosion problem at Mg chasis part in walkie talkie radio using cold spray technique. Current practise of corrosion treatment for Mg chassis structure is using organic coating contains no heavy metals, fluorides with no effect on the alloy composition upon recycling. Disadvantage of this technique is galvanic corrosion at Mg chassis part after 48hrs of salt spray testing and dull finishing. There is keen interest to explore potential applications of high pressure cold spray (HPCS) process onto Mg structure for corrosion treatment. One of the characteristic of cold spray process is creates a negligible heat-affected zone in the as-deposited material and substrate, therefore generating layers that exhibit excellent fatigue characteristics and spray efficiency in HPCS reaching up to 90%. Due to this features, cold spray is potential solution for corrosion treatment to be applied on Mg chassis structure